Quality Improvement in the Crude Palm Oil Production Process Using The Fuzzy Failure Mode and Effect Analysis Method - Ardi Saputra; Nazaruddin Nazaruddin; Muhammad Nur; Muhammad Isnaini Hadiyul Umam; Suherman Suherman (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Crude palm oil (CPO) is the main product of PT SBP. To produce crude palm oil (CPO), the company tests the moisture content, free fatty acid concentration, and impurity content to ensure its quality. PT SBP's CPO production process is inseparable from the risks that can disrupt CPO production. Several factors such as too high free fatty acid (FFA), moisture content (MOIST), and dirt content (DIRT) have the potential to disrupt the CPO production process, which will have an impact on the goals and objectives of PT SBP.  The purpose of this research is to estimate the risk of failure of the production process using fuzzy failure mode and effect analysis (FMEA) technique. Applying fuzzy logic with Matlab 2013b software can help overcome the challenges or limitations of FMEA. In this study, the largest FRPN number as determined using fuzzy calculations is 883 for purchasing raw materials that are not dependent on quality. Thus, the suggestion for improvement is specifically to organize fruit delivery and pay attention to the proper maturity level of palm fruits. Keywords: CPO (Crude Palm Oil), Fuzzy FMEA, Matlab